The mirror field: an experimental novel - Ang, Natalie Shi Hui (Nanyang Technological University, 2022)
The Mirror Field is about book design and the experimental novel. The project aims to discover ways the materiality of the book can be manipulated to enhance the narrative without detracting from the reading experience. Through challenging conventions of storytelling in physical books, the end result will present an alternate approach to the reading experience while informing on opportunities for the future of book design. The content consists of a fictional text-based narrative in the mystery genre, which inquires into the role of print in an increasingly variegated media ecology. The explorations will delve into the form, the content, and additional media of the physical book, deconstructing traditions of book production in ways that add value to the plot.